Effects of food supply chain regulation - Mokrejšová, Veronika; Filipová, Alena; Zeman, Jiří (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
This paper analyses the effects of food supply chain regulation investigating a particular example of the Act No. 395/2009, on Significant Market Power in the Sale of Agricultural and Food Products and Abuse thereof, which came into force in February 2010 in the Czech Republic. The objective of this paper is to explore the impact of this regulation on suppliers, their negotiation position and the retailer-supplier relationship. One hundred and one retail food suppliers were approached via a questionnaire, and the results of the research demonstrate that the Act has improved neither the negotiation position of the majority of suppliers nor the relationship of suppliers with retailers. It was also proven that the Act would not bring any special advantage to small and medium sized enterprises or domestic companies.
Argumenta Oeconomica, 2018, Nr 2 (41), s. 337-356
Keywords: retail relationships within the food supply chain; effects of legislative regulation; self-regulation